Grazing livestock increases both vegetation and seed bank diversity in remnant and restored grasslands. (18th October 2020) - Kapás, Rozália E.; Plue, Jan; Kimberley, Adam; Cousins, Sara A.O.
Abstract: Questions: Restoring grasslands is of great importance to biodiversity conservation to counteract widespread, ongoing losses of plant species diversity. Using source populations in remnant habitats and increasing functional connectivity mediated by grazing animals within and between habitats can benefit grassland restoration efforts. Here we investigate how grazing contributes to vegetation and seed bank diversity and composition in remnant and restored grassland communities in fragmented landscapes. Location: Stockholm archipelago, Sweden. Methods: We investigated the effects of the presence or absence of grazing animals as potential elements of functional connectivity on grassland species composition in both the vegetation layer and in the seed bank. Species inventory and seed bank sampling were carried out in 2 m × 2 m plots in remnant grassland habitats and adjacent restored grasslands on former arable fields. Results: Species composition varied between remnant and restored grasslands, with management‐dependent species more common in remnant grasslands. Remnant habitats with active grazing management contained a higher number of species in both the vegetation and seed bank compared to restored grasslands, but grazing reduced dispersal limitation from higher distance to source populations for specialist species. Where grazing was absent fewer plant species occurred in both the vegetation and in the seed bank. Conclusion: Our results show that grazing livestock play a key role in facilitating both spatial and temporal dispersal in fragmented grasslands. This results in increased species diversity in the vegetation and the seed bank of grazed grasslands compared to those maintained by mowing only. Functional connectivity provided by grazing management increases the possibility for species establishment from both the below‐ground seed bank and the surrounding landscape, thus increasing the resilience of plant communities against disturbances or climatic changes. Abstract : Land‐use changes in the Stockholm archipelago resulted in small, fragmented remnant and restored grasslands established on former arable fields. In this study, we investigated how functional connectivity provided by traditional grazing management influences the establishment of grassland species among species‐rich remnant and species‐poor restored grasslands. We found that grazing increased the vegetation and seed bank diversity in these grasslands.